Microstructure characterisation and constitutive modelling of waterborne epoxy resin modified bitumen emulsion. Issue 14 (6th December 2022) - Li, Rui; Leng, Zhen; Wang, Haopeng; Partl, Manfred N.; Yu, Huayang; Tan, Zhifei; Raab, Christiane
ABSTRACT: From the pavement construction emission perspective, bitumen emulsion is considered more environment-friendly than conventional bitumen because of its much lower construction temperature. However, bitumen emulsion faces the major concern of low mechanical strength especially at high service temperatures. To improve the mechanical performance of bitumen emulsion, waterborne epoxy resin can be used as a modifier. Nevertheless, there still lacks fundamental understanding on the effects of waterborne epoxy resin on the microstructure and rheological performances of the residual bitumen of the emulsion. To fill this gap, this study aims to investigate the microstructure and develop the constitutive model of the waterborne epoxy resin-modified bitumen emulsion residue (WEBER). To achieve this objective, a confocal laser scanning microscopy was first adopted to characterise the microstructure of WEBER. The frequency sweep tests were then conducted, and the '2S2P1D' model was applied to simulate the WEBER's dynamic response at different loading frequencies. The results indicated that the waterborne epoxy resin formed a polymer-rich film around the bitumen phase in the emulsion residue when its content reached 3 wt%, and the '2S2P1D' model can well describe the WEBER's dynamic response at different loading frequencies.